Correction to: Psychiatric symptoms, risk, and protective factors among university students in quarantine during the COVID-19 pandemic in China - Shufang Sun; Simon B. Goldberg; Danhua Lin; Shan Qiao; Don Operario (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.